Rattlesnake Envenomation in Three Dairy Goats - Joseph Smith; David Kovalik; Anita Varga (Case Reports in Veterinary Medicine, 2015)
Cases of rattlesnake envenomation in dairy goats are lacking. These cases present three dairy goats presented to a veterinary referral hospital for envenomation of Northern Pacific Rattlesnake (Crotalus oreganus). Treatments and clinical characteristics reported are similar to those for llamas, alpacas, and horses. These cases suggest that quick treatment in the event of a bite may have a more favorable clinical response. Existing rattlesnake bite scoring systems applicable to other species may be applicable to goats, and existing respiratory pathology may predispose goats to a less favorable outcome.